2010
DOI: 10.1002/pros.21322
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiation of prostate smooth muscle cells in response to bacterial LPS

Abstract: Prostate SMCs are capable of responding to LPS in vitro by dedifferentiating from a contractile to a miofibroblastic-like phenotype and secreting cytokines, with the TLR4 signaling pathway being involved in this response. In this way, prostate SMCs may contribute to the pathophysiology of inflammatory diseases by modifying the epithelial-stromal interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 29 publications
6
28
0
1
Order By: Relevance
“…For example, Cal is downregulated in dedifferentiated vascular SMCs (Shanahan et al, 1993) and after LPS challenge in rat prostate SMCs (Leimgruber et al, 2011) or after treatment of mouse vascular SMC with osteopontin (Gao et al, 2012).…”
Section: Partial Loss Of Contractile Marker Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cal is downregulated in dedifferentiated vascular SMCs (Shanahan et al, 1993) and after LPS challenge in rat prostate SMCs (Leimgruber et al, 2011) or after treatment of mouse vascular SMC with osteopontin (Gao et al, 2012).…”
Section: Partial Loss Of Contractile Marker Proteinsmentioning
confidence: 99%
“…Cal is a sensitive marker for the SMC contractile phenotype and exits in two isoforms (Sobue et al, 1999). Basic Cal is specific to SM tissues (Takahashi & Nadal-Ginard, 1991;Strasser et al, 1993) and is known to be regulated by inflammatory factors (Leimgruber et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Stereotypical lesions and intracellular reorganization of the smooth-muscle cells in various diseases indicate common molecular mechanisms of destruction of the ultrastructures and involvement of the leiomyocytes in pathological processes. Smooth-muscle cells constitute the stroma for prostatic glandular epithelium and through paracrine regulation mechanisms modulate the epitheliocyte proliferation, differentiation, and apoptosis and the glandular structures morphogenesis [6,7,13]. The epithelial-stromal interactions play the key role in realization of the hormonal and cytokine regulation of morphogenetic processes in health and neoplastic transformations.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested in the same study that prostatic smooth muscle cells become secretory cells in response to E. coli. Additionally, Leimgruber et al described a dedifferentiation process of smooth muscle cells after bacterial LPS treatment, with a loss of cytoskeleton molecules that characterized contractile phenotype (8). In another recent study, it was shown that inflammation caused the loss of smooth muscle cells around prostate ducts (24).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent papers showed that prostatitis elicited by E. coli caused an uncontrolled growth in the prostate gland at the early stages of inflammation (8,9). On the other hand, in previous studies, it was shown that uropathogenic E. coli or bacterial lipopolysaccharide (LPS) treatment causes hypocontractility in various tissues, including vessels, the urinary bladder, the corpus cavernosum, and the vas deferens (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%